Formulação de um herbicida biológico produzido através da fermentação submersa em biorreator. - Almeida, Thiago Castro de (2014)
The weeds can result in large losses in agricultural production and the main method of control is the use of chemical herbicides. Chemical herbicides are effective and great practicality, however bring direct and indirect consequences that cause different impacts on the environment. An important alternative to reduce the excessive use of chemical herbicides would be the use of biological control, including the use of phytotoxins as organic herbicides. A significant barrier in the production of organic products is the development of an economically viable process. The objectives of this study were to have a biological herbicide from the fungus Phoma sp. phytotoxin through a submerged fermentation,to optimize the formulations of the phytotoxin adjuvants together with the aid of various mixers and evaluate the herbicidal activity of the phytotoxin formulations on the control bioindicators. In submerged fermentation was used a bioreactor. The fermentation time was 5 days, other parameters used were rotation of 50 rpm, 15% dissolved oxygen, of 6.0 pH and aeration ranging from 1.0 to 7.0 L / min.Ultrasound showed the best results, in general, for the physicochemical properties studied, for example the formulations has remained stable with different concentrations together phytotoxin of Silwet L-77 and Aporte Plus.The evaluation of the possible action herbicide was divided in primary screening and secondary screening, with 17 formulations of the Central Composed Delineation Rotaticional (CCRD) made by ultrasound and turrax stirrer. At primary screening was performed by germination tests on seeds of cucumber (Cucumis sativus) and sorghum (Sorghum bicolor). The germination results obtained for control on cucumber seeds ranged from 57.0% to 100%, as in the 45.1% to 100% sorghum. Tests showed that 100% germination control for cucumber and sorghum, were the tests 10, 12, 14 and the central points. Secondary Screening was with the application of the formulations on four bio-indicator species have emerged more than 15 days, where dicotyledon were the lettuce (Lactuca sativa L) and cucumber (Cucumis sativus.), And Monocotyledon (Allium cepa L. - Alliaceae) and sorghum (Sorghum bicolor), determined the possible action herbicide in post-emergence. The results of 17 tests CCRD were similar to the experiment in preemergence tests having 10, 12, 14 and the midpoints of the top herbicidal effects, control of 100%.